Design and Implementation of Modular Multilevel Converter for Photovoltaic Energy Generation Using Hill Search Method - K, Rachananjali; R, Dr Srinu Naik (International Journal of Engineering and Technology, 2018)
This article proposes an approach to capture solar energy utilizing double energy conversion from DC-DC and DC-AC.Â The present scenario requires lot of energy in order to meet the demand; the energy generation without hurting the environment is possible by means of non-conventional sources. In this article the source chosen is solar energy. To capture solar energy, solar cell is utilized. On capturing the solar energy the achieved result is in the form of DC. The DC link is established and it is boosted with the help of DC-DC converter and it is being fed as input to modular multilevel converter (MMC) which provides us with the desirable AC output. To escalate the performance of the system hill search which is one of the maximum power point tracking (MPPT) technique is being implemented. The performance of the proposed system is being verified by simulation results and results are validated.